Modulation of Inflammation-Related Lipid Mediator Pathways by Celastrol During Human Macrophage Polarization - Zhang K; Jordan PM; Pace S; Hofstetter RK; Werner M; Chen X; Werz O (Dove Medical Press, 2022)
Kehong Zhang,1,2 Paul Mike Jordan,1 Simona Pace,1 Robert K Hofstetter,1 Markus Werner,1 Xinchun Chen,2 Oliver Werz1 1Department of Pharmaceutical/Medicinal Chemistry, Institute of Pharmacy, Friedrich Schiller University Jena, Jena, D-07743, Germany; 2Guangdong Provincial Key Laboratory of Regional Immunity and Diseases, Department of Pathogen Biology, Shenzhen University School of Medicine, Shenzhen, 518000, People's Republic of ChinaCorrespondence: Oliver Werz, Email oliver.werz@uni-jena.deBackground and Purpose: Celastrol (CS) is a major active ingredient of the Chinese/Asian herb Tripterygium wilfordii that is frequently used as phytomedicine to treat inflammation and autoimmune diseases. We showed before that short-term exposure to CS (1 μM) favorably impacts the biosynthesis of inflammation-related lipid mediators (LM) in human polarized macrophages by modulating the activities of different lipoxygenases (LOXs). However, whether CS regulates the expression of LOXs and other related LM-biosynthetic enzymes during macrophage polarization is unknown. Here, we investigated how CS affects LM-biosynthetic enzyme expression on the protein level and studied concomitant LM signature profiles during polarization of human monocyte-derived macrophages (MDM) towards M1- and M2-like phenotypes.Methods and Results: We used LM metabololipidomics to study the long-term effects of CS on LM profile signatures after manipulation of human monocyte-derived macrophages (MDM) during polarization. Exposure of MDM to low concentrations of CS (ie, 0.2 μM) during polarization to an inflammatory M1 phenotype potently suppressed the formation of pro-inflammatory cyclooxygenase (COX)- and 5-LOX-derived LM, especially prostaglandin (PG)E2. Notably, gene and enzyme expression of COX-2 and microsomal PGE2 synthase (mPGES)-1 as well as M1 markers were strongly decreased by CS during M1-MDM polarization, along with impaired activation of nuclear factor-κB and p38 mitogen-activated protein kinase. During IL-4-induced M2 polarization, CS decreased the capacity of the resulting M2-MDM to generate pro-inflammatory COX and 5-LOX products as well but it also reduced the formation of 12/15-LOX products and specialized pro-resolving mediators, without affecting the levels of liberated fatty acid substrates.Conclusion: Depending on the timing and concentration, CS not only favorably affects LOX activities in macrophages but also the expression of LM-biosynthetic enzymes during macrophage polarization connected to changes of inflammation-related LM which might be of relevance for potential application of CS to treat inflammatory disorders.Graphical Abstract: Keywords: inflammation, macrophages, lipoxygenase, cyclooxygenase, lipid mediators, specialized pro-resolving mediators, celastrol